Public insight into knee osteoarthritis: a cross-sectional study from the West Bank, Palestine - Haya Jebreen Mohammed Warasna; Bashar Yaser Hasan Awad; Mohamad A. Banat; Mohammad Yaser Hasan Awad; Ahmed Farid Gadelmawla; Jameel Suliman; Tarek A. Owais; Ahmad J. Warasna (BMC Public Health)
Abstract Background Osteoarthritis (OA) is a significant global health concern and is characterized by the degeneration of joint structures, leading to pain, stiffness, and functional limitations It is estimated that 654.1 million individuals are affected by osteoarthritis worldwide, with females, especially those older than 60 years of age, being the population most impacted. However, there remains a gap in understanding the awareness of knee osteoarthritis among specific populations, such as the Palestinian community in the West Bank, thus, highlighting the need for targeted research to address this health disparity. Methods A cross-sectional survey was conducted in the West Bank from August to September 2024. Participants were recruited from 11 cities and a validated questionnaire adapted from a previous study was used to collect the data. The reliability of the questionnaire was assessed using Cronbach’s alpha, yielding a value of standard alpha = 0.71, which is an acceptable value. The survey collected demographic data, clinical characteristics, knowledge of osteoarthritis risk factors, symptoms, and attitudes towards treatment options. R Statistical Software was used for data analysis, which included descriptive statistics, chi-square tests, and logistic regression to explore the relationships between demographic factors and osteoarthritis knowledge, whereby a p-value of ≤ 0.05 was set up as a significance level. Results A total of 725 valid responses were included in our study. Among the participants, 569 were female, predominantly aged 25 or younger (66%, n = 479), and 62% (n = 450) were single. Knowledge assessment revealed that 80% (n = 580) recognized knee osteoarthritis as a chronic disease, while only 51% (n = 369) understood its impact on joint involvement. The majority identified high BMI (87%, n = 632), advancing age (94%, n = 683), and previous knee injury (72%, n = 520) as risk factors, although only 42% (n = 306) acknowledged genetics as one. Most participants were aware of the management strategies, including analgesics (70%, n = 510) and physiotherapy (80%, n = 579). However, 66% (n = 478) scored low for overall knowledge regarding knee osteoarthritis. Conclusion This study emphasizes the critical importance of raising awareness and knowledge about osteoarthritis within the Palestinian community. Despite being widely known as a long-term issue, there are still noticeable gaps in the understanding of the joint impact, potential risks, and effective treatment methods for osteoarthritis. The use of informal sources highlights the importance of specific educational programs by healthcare providers.